The Effect of Stirring on the Morphology of Birnessite Nanoparticles. (4th June 2008) - Cheney, Marcos A.; Bhowmik, Pradip K.; Moriuchi, Shingo; Villalobos, Mario; Qian, Shizhi; Joo, Sang W.
Abstract : The effect of mechanical stirring on the morphology of hexagonal layer-structure birnessite nanoparticles produced from decomposition ofKMnO 4 in dilute aqueousH 2 SO 4 is investigated, with characterization by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), high-resolution transmission electron microscopy (HRTEM), thermogravimetric analysis (TGA), andN 2 adsorption (BET). Mechanical stirring during an initial stage of synthesis is shown to produce black birnessite containing nanofibers, whereas granular particulates of brown birnessite are produced without stirring. This is the first reduction synthesis of black birnessite nanoparticles with dendritic morphology without any use of organic reductant, and suggests that a particular morphology can arise from structural preferences of Mn in acidic conditions rather than particular organic reactants. These results enlighten the possibility of synthesizing nanoparticles with controlled size and morphology.